1977
DOI: 10.1073/pnas.74.1.268
|View full text |Cite
|
Sign up to set email alerts
|

Cell differentiation in Dictyostelium under submerged conditions.

Abstract: Hitherto it has not been possible to obtain spore and stalk cell differentiation of the cellular slime molds in submerged cultures. It is shown here that cells when elaced in roller tubes under an atmosphere of oxygen, will form clumps and differentiate in 48-72 hr into mature spores and stalk cells. Although differentiation occurs without the normal morphogenetic movements, there is the appearance of an anteroposterior polarity of the cells in the clump. In addition to oxygen we examined a number of other fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…Another function for O 2 in Dictyostelium, cytochrome oxidase subunit VII switching (Sandona et al, 1995), does not involve P4H1 based on DNA microarray studies (L. Eichinger and C.M.W., unpublished). The role of P4H1 in O 2 -dependent slug polarization and guidance of slug migration (Sternfeld and Bonner, 1977;Sternfeld and David, 1981) remains to be examined. Because hypoxic regulation is connected with sporulation, Dictyostelium offers a unique genetic opportunity to investigate the mechanism of P4H1 action, including its role as a direct O 2 sensor and the identification of upstream and downstream regulatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…Another function for O 2 in Dictyostelium, cytochrome oxidase subunit VII switching (Sandona et al, 1995), does not involve P4H1 based on DNA microarray studies (L. Eichinger and C.M.W., unpublished). The role of P4H1 in O 2 -dependent slug polarization and guidance of slug migration (Sternfeld and Bonner, 1977;Sternfeld and David, 1981) remains to be examined. Because hypoxic regulation is connected with sporulation, Dictyostelium offers a unique genetic opportunity to investigate the mechanism of P4H1 action, including its role as a direct O 2 sensor and the identification of upstream and downstream regulatory genes.…”
Section: Discussionmentioning
confidence: 99%
“…Cytochrome oxidase subunit VII is encoded by two genes whose expression is oppositely regulated by O 2 tension (60). Culmination, the final morphogenetic step in sporulation, and terminal cell differentiation also require nearly normal O 2 tension (60,61). The polarity and direction of migrating slugs appear to be influenced by O 2 levels (62).…”
Section: Discussionmentioning
confidence: 99%
“…Lack of sufficient oxygen is the principal factor limiting development in clumps of cells in submerged culture [3,4]. If the oxygen concentration is increased, development occurs in submerged cultures and the cells in clumps differentiate into stalk cells and spores.…”
Section: Submerged Culture Methodsmentioning
confidence: 99%
“…While these results indicate that prestalk-prespore interconversion requires a relatively long time compared to the rapid sorting of anterior and anterior-like cells, they do not preclude the existence of more rapid differentiation events. For example, Gregg [37] observed that, within 15-30 min after isolation of the prestalk zone, some cells incorporate 3 An interesting feature of the sorting mechanism is the localization of an extracellular signal -in this case the chemotactic agent -in one region of the slug. Such localization of a signal could be used by the organism to stimulate differentiation of cells in that region without affecting cells elsewhere in the slug.…”
Section: Cell Type Conversion During Pattern Regenerationmentioning
confidence: 99%
See 1 more Smart Citation